Dynamics of marketability structure of pine stands in Slobozhanskyi forest typological district - Пастернак , В. П.; Гірс , О. А.; Гармаш , А. В. (Forestry and Forest Melioration, 2023)
Introduction At the current stage, the development of regulatory and informational materials for evaluating and forecasting the dynamics of the marketability structure of stands of the main forest-forming species, taking into account zonal features, is relevant. Scots pine (Pinus sylvestris L.) is one of the most widespread tree species in the study area. In this regard, the development of standards for pine stands of artificial origin in the study region is important for sustainable forest management. The aim of the research was to establish features of the dimensional and marketability structure of planted pine stands in Slobozhanskyi forest typological district. Materials and Methods The Forest Fund database was used to analyze the distribution of pine stands in Slobozhanskyi forest typological district by origin, forest types, density of stocking, and productivity. For a detailed study of the dimensional and marketability structure, 40 sample plots in the planted pine stands were laid out; additionally, 10 sites with pre-cutting assessment for final felling were used. The theoretical series of diameter distribution was built according to the methodology developed at the Department of Forest Mensuration and Forest Management of NULES of Ukraine. The parameters of the stand structure were obtained using the STRUK and BUDOVA programs. Results According to the data of the Forest Fund database as of January 1, 2017, the pine forests in the study region cover an area of more than 180 thousand hectares. Almost 90% of the pine stands are of artificial origin. The pine stands grow mostly in fresh relatively poor forest site condition (70%); the share of fresh relatively rich and fresh poor sites is 10 and 11%, respectively. The majority of the pine stands have a medium density of stocking and the 1st site class. The results of calculating the indicators of the dimensional structure show that the ?-distribution is optimal for the object of study. The variability of diameters in artificial pine stands in Slobozhanskyi forest typological district is lower (22.0%) compared to 30.1% for the Forest-Steppe and Polissia as a whole, 41.2% for the protected forests of the Central Polissia, and 23.7% for the Prydonetskyi Steppe. The yield of industrial timber is higher for the Slobozhanskyi forest typological district compared to the Prydonetskyi Steppe (7.1% on average). It is explained both by the slightly lower total growing stock and by the worse condition of the pine stands in the Prydonetskyi Steppe. According to our data, the yield of industrial wood is slightly higher than for modal natural pine stands in Kyiv region, which is explained primarily by different standards for evaluating industrial timber, as well as slightly lower total stocks and features of the dimensional structure of natural pine forests in Kyiv region. Conclusions The pine stands of Slobozhanskyi forest typological district are significantly different from the stands of Prydonetskyi Steppe and Polissia of Ukraine in terms of growth dynamics and marketability. Therefore, the regulations of the dimensional structure and the dynamics of the marketability structure of modal pine stands, taking into account the European approaches to the mensuration of round timber, presented in this article, can significantly improve the quality of forestry management and the accuracy of forest mensuration of pine stands in Slobozhanskyi region. It has been established that technical maturity for industrial timber occurs at the age of 70 years, for industrial timber with a median diameter without bark of more than 19.5 cm it occurs at 90 years and more than 29.5 cm at 100 years. 2 Figs., 4 Tables, 14 Refs.